“Batizamos e aceitamos pessoas homoafetivas”:um estudo sobre a produção de discursos acerca de sexualidades não hegemônicas na Igreja Batista do Pinheiro, Maceió/AL - Coelho Júnior, Carlos Lacerda (2019)
The first studies in the field of Brazilian Social Sciences, which intersect the issues of sexual and gender diversity and Christian religiosity, basically emerged at the turn of the twentieth to the twenty-first century. The existing literature, which emphasizes the intertwining of these categories, is still quite scarce and more common in the field of social anthropology, pointing to the real need for conducting research that intends to apprehend, in contemporary times, the power relations crossed in the context of evangelical churches and inclusive denominations regarding LGBTI identities. The emergence of this phenomenon is permeated by a number of social factors, such as the transformations of intimacy, the increasing appreciation of individual freedoms, achievements within the scope of social visibility and rights through struggles waged by social movements such as the Brazilian Homosexual Movement, as well as the rapid growth of evangelical religions, significantly altering the national religious landscape. In this sense, this research aims to understand, in the light of theoretical contributions provided by sociology, the processes by which led a traditional evangelical church of the city of Maceió – Baptist Church of Pinheiro – to become inclusive to the LGBTI public as well as understand the relations between sexual careers, construction of a Christian identity and the constitution of a new self among homosexual adherents of the referred religious denomination